Physical properties of In2O3 thin films prepared at various oxygen partial pressures - Kaleemulla, S. (2009)
http://www.sciencedirect.com/science/article/B6TWY-4VDS8C6-5/2/b17183c97b173ec8a28b25ffd97e054c